A multiwalled-carbon-nanotube-based biosensor for monitoring microcystin-LR in sources of drinking water supplies - Han, C.; Doepke, A.; Cho, W.; V. Likodimos; de la Cruz, A.A.; Back, T.; Heineman, W.R.; Halsall, H.B.; Shanov, V.N.; Schulz, M.J.; P. Falaras; Dionysiou, D.D. (Advanced Functional Materials, 2013)
A multiwalled carbon nanotube (MWCNT)-based electrochemical biosensor is developed for monitoring microcystin-LR (MC-LR), a toxic cyanobacterial toxin, in sources of drinking water supplies. The biosensor electrodes are fabricated using vertically well-aligned, dense, millimeter-long MWCNT arrays with a narrow size distribution, grown on patterned Si substrates by water-assisted chemical vapor deposition. High temperature thermal treatment (2500 °C) in an Ar atmosphere is used to enhance the crystallinity of the pristine materials, followed by electrochemical functionalization in alkaline solution to produce oxygen-containing functional groups on the MWCNT surface, thus providing the anchoring sites for linking molecules that allow the immobilization of MC-LR onto the MWCNT array electrodes. Addition of the monoclonal antibodies specific to MC-LR in the incubation solutions offers the required sensor specificity for toxin detection. The performance of the MWCNT array biosensor is evaluated using micro-Raman spectroscopy, including polarized Raman measurements, X-ray photoelectron spectroscopy, cyclic voltammetry, optical microscopy, and Faradaic electrochemical impedance spectroscopy. A linear dependence of the electron-transfer resistance on the MC-LR concentration is observed in the range of 0.05 to 20 μg L-1, which enables cyanotoxin monitoring well below the World Health Organization (WHO) provisional concentration limit of 1 μg L-1 for MC-LR in drinking water. An highly sensitive Faradaic electrochemical impedance biosensor for monitoring microcystin-LR (MC-LR) in sources of drinking water supplies is developed using millimeter-long multiwalled carbon nanotube (MWCNT) arrays grown by water-assisted chemical vapor deposition with vertical alignment. A linear sensing response shows a wide microcystin-LR concentration range that is below the World Health Organization (WHO) provisional guideline limit of 1 μg L-1 for MC-LR in drinking water. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.